Population parameters in Brazilian Thoroughbred - Taveira, R. Z.; Mota, MDS; Oliveira, H. N. (Blackwell Verlag Gmbh, 2004)
The information in this study has been provided by the Brazilian Association of Racehorse Breeders [Associação do Brasileira dos Criadores do Cavalo de Corrida (ABCCC)]. It can be found in the files on the CD-ROM developed by the ABCCC in 1999. A total of 5008 finishing time records related to 2545 winning horses that ran in the classical calendar on Brazilian hippodromes during 25 years (197498) were analysed. There were a total of 9949 horses on the relationship matrix. The variance components were estimated using the multiple-trait derivate-free restricted maximum likelihood (MTDFREML) program, for an animal model. Generation intervals were higher in the maternal side (10.91 years) than in the paternal one (10.41 years). The estimates for genetic permanent environmental and phenotypic variances and heritability were 0.291, 0.161, 3.486 and 0.08, respectively. The phenotypic standard deviation for time in races was 1.86729 s. Genetic time trend on Thoroughbred races in Brazil was small and could be accelerated if selection considered the trait time effectively. With respect to the animal's country of birth, the results show that there has been an intense participation of foreign animals in breeding Brazilian Thoroughbreds.